The Assessment of Trait Emotional Intelligence: Psychometric Characteristics of the TEIQue-Full Form in a Large Italian Adult Sample - Chirumbolo, Antonio; Picconi, Laura; Morelli, Mara; Petrides, K. V. (Frontiers in Psychology, 2019)
Trait Emotional Intelligence (or trait emotional self-efficacy) represents a set of dispositions and self-perceptions related to emotions, placed at the lower levels of personality hierarchies. This paper examined the psychometric features of the Trait Emotional Questionnaire Full Form (TEIQue-FF) in the Italian context by investigating its reliability and dimensionality. Incremental validity in the prediction of depression and anxiety was also tested with respect to the Big Five. Participants were 1343 individuals balanced for gender (690 females and 653 males) whose mean age was 29.65 years old (SD = 13.64, range 17 – 74 y.o.). They completed a questionnaire containing the TEIQue and measures of the Big Five, depression, and anxiety (both trait and state). Results indicated that the performance of the TEIQue-FF in the Italian context was comparable to the original English version as regards its reliability and factor structure. Moreover, the instrument showed incremental validity in the prediction of depression and state-trait anxiety over and above the Big Five.